SOCIAL PARTICIPATION AND TOURISM PUBLIC POLICY: THE BRAZILIAN TOURISM REGIONALIZATION PROGRAM - Minasi, Sarah Marroni; Kaizer, Éverton; Mesquita, Rodrigo (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Issues of governance, collaboration, and participation are at the forefront of much tourism public management on finding new alternatives to tourism destinations development. This paper aims to diagnose the performance of social participation in the Brazilian Tourism Regionalization Program from 2004 to 2020. This research has a qualitative approach with data collected through bibliographic and documentary research covering 2004 to 2020. The data collected were analyzed according to categories defined by the literature. We analyzed eleven Tourism Regionalization Program documents and 13 specific published articles on tourism governance instances in the Tourism Regionalization Program. As a result, we observe that social participation went from a fundamental issue in 2004 to a prerequisite for integrating a tourist region in 2020. And they are now suppressed by the targeting of protagonism for the private sector. The results of this research advance the theoretical discussions regarding social participation in Brazilian tourism’s regionalization. The synthesis of the analyses and discussions promoted the need to rethink organizing tourism governance in the Brazilian case to meet the demand for social participation and the regional development of tourism.